1998
DOI: 10.1099/00207713-48-4-1405
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium hibernum sp. nov., a lactose-utilizing bacterium from a freshwater Antarctic Lake

Abstract: Four freshwater Antarctic lakes were examined for the presence of pgalactosidase-producing bacteria using mineral medium enrichments and lactose. Enrichments from only one of the lakes produced growth and two strains were isolated that were very similar in phenotype and fatty acid profile, and shared considerable homology in their DNA (DNA-DNA hybridization = 9327 YO). The strains were psychrotrophic with theoretical T,,,,,, Tmin and To,, of 30-31, -7 O and 26 "C, respectively. The P-galactosidase in cell extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 20 publications
(12 reference statements)
1
33
0
Order By: Relevance
“…Growth at 25 mC on agar (j) (j) (j) j j j j j k j j j j j Gliding motility k j k j j j k j (j) j j j j j Flexirubins k k k k j k k j j j j j j k Glucose utilization j j j j j   k k j j j j j Acid from carbohydrates j j j j j j j k k j j j j j Bernardet et al (1996), McCammon et al (1998) and this study.…”
Section: Charactermentioning
confidence: 99%
See 1 more Smart Citation
“…Growth at 25 mC on agar (j) (j) (j) j j j j j k j j j j j Gliding motility k j k j j j k j (j) j j j j j Flexirubins k k k k j k k j j j j j j k Glucose utilization j j j j j   k k j j j j j Acid from carbohydrates j j j j j j j k k j j j j j Bernardet et al (1996), McCammon et al (1998) and this study.…”
Section: Charactermentioning
confidence: 99%
“…Lactose-utilizing isolates from a highly oligotrophic freshwater lake in the Vestfold Hills were described as Flavobacterium hibernum by McCammon et al (1998). Finally a number of yellow-and orange-pigmented isolates from sea ice and marine salinity lake samples (Franzmann et al, 1990 ;Bowman et al, 1997a) have been found to be phylogenetically related to the genus Flavobacterium ; however 16S rRNA sequence data suggested these strains represent potentially novel species.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the genus comprises more than 69 species with validly published names, with Flavobacterium aquatile as the type species. Members of the genus have been isolated from various habitats, such as freshwater (Wang et al, 2006;Tamaki et al, 2003), soil (Bernardet et al, 1996;Tamaki et al, 2003;McCammon & Bowman, 2000;Liu et al, 2008), glacier (Zhu et al, 2003), Antarctic lakes (Van Trappen et al, 2003, 2004McCammon et al, 1998;McCammon & Bowman, 2000;Humphry et al, 2001;Yi et al, 2005) and marine sediments (Fu et al, 2011). In addition, three Flavobacterium species are pathogenic to fish (Bernardet & Bowman, 2006).…”
mentioning
confidence: 99%
“…Owing to the continuous exploration of extreme environments, the genus has expanded considerably, especially with psychrophilic and psychrotolerant species. Among published species of the genus Flavobacterium, 25 are coldadapted organisms, of which 14 were isolated from the Antarctic (Humphry et al, 2001;McCammon & Bowman, 2000;McCammon et al, 1998;Van Trappen et al, 2003Yi & Chun, 2006;Yi et al, 2005) and eight from glaciers in China (Dong et al, 2012; Xin et al, 2009; Xu et al, 2011;Zhang et al, 2006;Zhu et al, 2003Zhu et al, , 2013.Strains NP180 T and NR80 were isolated from Nam Co lake located in Tibet in the west of China, at an altitude of 4718 m (30 u 309 N 90 u 169 E); the annual mean water temperature is 10-15 u C. Samples of lake water were collected and 10-fold dilutions were plated on PYG agar (5.0 g Bacto peptone, 0.2 g yeast extract, 5.0 g glucose, 3.0 g beef extract, 0.5 g NaCl, 1. 1000 ml sterile water, 15 g agar, pH 7.0).…”
mentioning
confidence: 99%